1H, 13C and 31P NMR Studies of 2-(Substituted Phenoxy) 2,3-Dihydro-1H-Naphtho- [1,8-de]-1,3,2-Diazaphosphorine-2-oxides - Devendranath Reddy, C.; Tirupathi Reddy, G.; Reddy, M.S. (Asian Journal of Chemistry, 2010)
NMR data for title compounds show that diazaphosphorine 2-oxide system does not exert significant influence on the aryloxy protons. The P–C coupling constants provide support for the half chair conformation of the diazaphosphorine ring with equatorial orientation of the aryloxy group. The 31P signals appeared over a wide region –6.35 to –5.27 ppm showing that the 31P chemical shifts are sensitive to subtle differences in the structure of the molecules and stereo electronic environment. The NH proton signal appeared as a doublet in downfield at δ 8.1–8.7 (2JP–N–H=5.4–6.0 Hz) due to its coupling with phosphorus.